1992
DOI: 10.1002/aja.1001930306
|View full text |Cite
|
Sign up to set email alerts
|

Expression of sarcomeric myosin in the presumptive myocardium of chicken embryos occurs within six hours of myocyte commitment

Abstract: The distribution of sarcomeric myosin heavy chain (MyHC) has been examined immunoctochemically in the presumptive myocardial cells of chicken embryos (stages 6-10) prior to the onset of the heart beat. Embryos were stained with monoclonal antibody MF20, a reagent which recognizes all chicken sarcomeric MyHCs (Bader et al., 19821, and then examined both in whole mount by immunofluorescence and in semithin, plastic-embedded sections following immunoperoxidase labeling. We observed that myosin could be detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…1). Differentiating heart muscle cells are first detected at stage 7 (Bisaha and Bader, 1991;Han et al, 1992); a beating heart tube is present by stage 10. Cells destined to form the myocardium pass through the rostral portion of the primitive streak during stage 3a-b (Garcia-Martinez and , migrate away from the streak and during stages 3c-d begin to form a loosely cohesive layer of cells sandwiched between endoderm and ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…1). Differentiating heart muscle cells are first detected at stage 7 (Bisaha and Bader, 1991;Han et al, 1992); a beating heart tube is present by stage 10. Cells destined to form the myocardium pass through the rostral portion of the primitive streak during stage 3a-b (Garcia-Martinez and , migrate away from the streak and during stages 3c-d begin to form a loosely cohesive layer of cells sandwiched between endoderm and ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…Although no above-background fluorescence was detected in these explants, it must nonetheless be considered these explants express cardiogenic traits that are below the level of detection by immunostaining for the sarcomeric actins, which appear relatively late in the cardiogenic sequence in vivo (Sugi and Lough, 1992). This question could be resolved by immunostaining for markers that appear earlier in the cardiogenic sequence, such as ventricular myosin heavy chain 1 (Bisaha and Bader, 1991) or sarcomeric myosin heavy chain (Han et al, 1992). Also, although it could be considered that cardiogenesis was inhibited in the ectodermimesoderm co-cultures by the inadvertent inclusion of neuroectoderm, the fact that central axis cells were rigorously excluded from the explants and that no evidence of neural tube structures was seen in the cultures make this unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The fulfillment of this objective requires the identification of embryonic cells that regulate heart development, using a n in vitro model system in which the cardiogenic effects of cellular secretions can be studied under defined cell culture conditions. For this purpose we have employed the avian cardiogenic model, using explanted endoderm and mesoderm cells from the HFR at stage 6; at this precardiac stage in vivo, terminal cardiogenic traits such as ventricular myosin heavy chain 1 (Bieaha and Bader, 19911, sarcomeric myosin heavy chain (Han et al, 1992), or cardiac alpha-actin are not expressed. Preliminary experiments in which endoderm and mesoderm cells were co-cultured on thick collagen gels in fortified medium indicated that endoderm has a role in the regulation of terminal cardiogenesis (Lough et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with these morphological events, the cells within these heart fields begin to show evidence of a cardiac phenotype. By the time the fusion of the heart fields is initiated, several contractile proteins are exhibited in a prestriated pattern by the cardiogenic cells (Tokuyasu and Maher, 1987a, b;Ruzicka and Schwartz, 1988;de Jong et al, 1990;Bisaha and Bader, 1991;Han et al, 1992;Colas et al, 2000). Concomitant with the first appearance of striated muscle by the 10 somite stage (HH stage 10 in the chick) is the first display of beating by the primitive heart.…”
Section: Cardiac Tissue Formation In the Vertebrate Embryo-a Synopsismentioning
confidence: 99%